2022
DOI: 10.1039/d2tc00483f
|View full text |Cite
|
Sign up to set email alerts
|

Protein-based (bio)materials: a way toward high-performance graphene enzymatic biosensors

Abstract: Enzymes are ideal receptors for biosensors since they offer excellent selectivity and high catalytic activity. However, once removed from their native environment, enzymes present a short lifespan determining a huge...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…[ 85 ] We recently demonstrated that the integration of CTPR protein films in the design of enzymatic sensors can extend their lifespan from a few days to more than six months improving the repeatability and reproducibility as well. [ 85 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 85 ] We recently demonstrated that the integration of CTPR protein films in the design of enzymatic sensors can extend their lifespan from a few days to more than six months improving the repeatability and reproducibility as well. [ 85 ]…”
Section: Resultsmentioning
confidence: 99%
“…The physical entrapment of these biomolecules in the protein film results in improved thermal stability [39] and extended enzymatic activity over time. [85] We recently demonstrated that the integration of CTPR protein films in the design of enzymatic sensors can extend their lifespan from a few days to more than six months improving the repeatability and reproducibility as well. [85] With the aim to exploit this great advantage of CTPR proteins, we introduced glucose oxidase (GOx) in the ink formulation.…”
Section: Detection Of Glucosementioning
confidence: 99%
See 2 more Smart Citations
“…[39] This versatility makes them ideal candidates for interfacing with other functional elements and materials to create new types of materials. As evidence of its robustness and versatility, in previous studies CTPR proteins have been used as scaffolds to stabilize metallic clusters for bioimaging, [40] combined with graphene to improve the long-term performance of electrochemical sensors, [41][42][43] template gold nanoparticles at specific positions through bioconjugation to form self-assembled conducting materials, [44] organize carbon nanotubes and porphyrin by protein-material hybridization resulting in photoconductive systems, [45] and stabilize redox active FeS 2 clusters for electron transfer conduits. [46] Moreover, CTPR demonstrated wire-like performance as molecular electronic components, showing improvement compared with tailored molecules.…”
Section: Introductionmentioning
confidence: 99%